The main socio-cultural factors and the reasons for the need to form a culture of religious tolerance in Kazakhstan - Balpanov, N.; Ismagambetova, Z.; Karabayeva А. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2018)
In modern conditions for the Kazakh society one of the topical problems is the formation of a culture of religious tolerance in the Kazakh society. In this article, the authors set out to determine the main social factors that can have a negative impact on the preservation of the stability of society and the cultural and religious security of the country. The authors note the influence of globalization and modernization on interfaith and interethnic relations. The authors note some of the threats that exist in society. The article gives an analysis of the types of migration in the country. The authors disclose a number of social consequences of urbanization, creating threats to maintaining stability in society. Key words: tolerance, religious tolerance, migration, urbanization, modernization.